The Impact of Philosophizing Training on Students' Inquisitiveness and Creative Thinking - Sadeghi, Zahra; Hamedi, Afifeh (Iranian Journal of Educational Sociology, 2022)
Purpose: The present study aimed to investigate the impact of philosophizing training on the inquisitiveness and creative thinking of sixth-grade students in Bushehr County.Methodology: This research method was among quasi-experimental studies. The statistical population consisted of 4,263 sixth-grade students in Bushehr County. The sample size included 40 students, obtained through cluster random sampling. The tools for data collection in this study were the Heydari Inquisitiveness Questionnaire (2013) and the Wiles and Dowell Creative Thinking Questionnaire (2002). The obtained data were analyzed using univariate and multivariate covariance analysis.Findings: The findings showed that the adjusted mean score of the inquisitiveness variable in the experimental group's post-test stage was higher than that of the control group. Therefore, it can be said that philosophizing training led to an increase in the inquisitiveness of the experimental group compared to the control group, indicating the positive impact of philosophizing training on the inquisitiveness of the experimental group relative to the control group. Additionally, the adjusted mean score of the creative thinking variable in the experimental group's post-test stage was higher than that of the control group. Therefore, it can be said that philosophizing training led to an increase in the creative thinking of the experimental group compared to the control group, indicating the positive impact of philosophizing training on the creative thinking of the experimental group relative to the control group.Conclusion: Therefore, philosophizing training were effective for improving inquisitiveness and creative thinking in sixth-grade students.